نمذجة العلاقة بين أسعار النفط الدولية وأسعار صرف العملات الإرتكازية باستخدام نماذج الـ VAR خلال الفترة ( 1999 - 2013 ) - معزوز، لقمان (المدرسة العليا للتجارة - مخبر الإصلاحات الإقتصادية، التنمية واستراتيجيات الإندماج في الإقتصاد العالمي, 2014)
Has undergone a causal relationship between crude oil prices and currency exchange rates are basic - primarily the dollar and the Euro - for many economic studies that have reached inconclusive results, and assuming a causal relationship a two-way between the dollar exchange rate against the euro and international oil prices during the period (1999-2013) problem manifested a mutual nature of the trends between crude oil prices and the dollar exchange rates and the Euro? Is there a causal relationship between the two?. The study concluded form the VAR and causal Granger and functions response (shock) and variance analysis that there is a strong correlation and statistical significance between international oil prices and exchange rates of the dollar against the Euro, where we found that the flexibility of oil prices for the growth of exchange rates of the dollar against the Euro is estimated -0.44% in the short term, and flexible exchange rates of the dollar against the Euro for the growth of oil prices estimated 0.016%.
خضعت العلاقة السببية بين أسعار النفط الدولية وأسعار صرف العملات الارتكازية - وفي مقدمتها الدولار والأورو- للعديد من الدراسات الاقتصادية التي توصلت إلى نتائج غير حاسمة، وبافتراض الدراسة وجود علاقة سببية ذات اتجاهين بين سعر صرف الدولار مقابل الأورو وأسعار النفط الدولية خلال الفترة (1999- 2013) تتجلي الإشكالية بوضوح، وهي ما طبيعة الاتجاهات المتبادلة بين أسعار النفط الخام وأسعار صرف الدولار والأورو؟ وهل هناك علاقة سببية بينهما؟ وقد خلصت الدراسة من خلال نموذج ال VAR وسببية Granger ودوال الاستجابة (الصدمات) وتحليل التباين إلى أن هناك علاقة متبادلة قوية، وذات دلالة إحصائية بين أسعار النفط الدولية وأسعار صرف الدولار أمام الأورو، حيث توصلت الدراسة إلى أن مرونة أسعار النفط بالنسبة لنمو أسعار صرف الدولار أمام الأورو تقدر ب 0.44%- في الأجل القصير، ومرونة أسعار صرف الدولار أمام الأورو بالنسبة لنمو أسعار النفط تقدر ب -0.016%.
Keywords: النفط الخام -- أسعار النفط الدولية -- أسعار الصرف